2021
DOI: 10.1371/journal.pone.0257889
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly declines in protected areas of Illinois: Assessing the influence of two decades of climate and landscape change

Abstract: Despite increasing concern regarding broad-scale declines in insects, there are few published long-term, systematic butterfly surveys in North America, and fewer still that have incorporated the influence of changing climate and landscape variables. In this study, we analyzed 20 years of citizen science data at seven consistently monitored protected areas in Illinois, U.S.A. We used mixed models and PERMANOVA to evaluate trends in butterfly abundance, richness, and composition while also evaluating the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…The decline found in Picos de Europa butterfly abundance in the last 9 years is in line with previous studies from elsewhere (Brereton et al, 2019; Fox et al, 2023; Melero et al, 2016; Van Swaay et al, 2017, 2020; Wepprich et al, 2019), confirming a global butterfly declining trend, even in well‐established protected areas, which are nonetheless affected by global change drivers (Colom et al, 2019; Kuckerov et al, 2021). However, the annual 5.7% decline in abundance found doubles the maximum annual decline rates found in other studies, which range from −2.6% to −0.8% (see tab.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The decline found in Picos de Europa butterfly abundance in the last 9 years is in line with previous studies from elsewhere (Brereton et al, 2019; Fox et al, 2023; Melero et al, 2016; Van Swaay et al, 2017, 2020; Wepprich et al, 2019), confirming a global butterfly declining trend, even in well‐established protected areas, which are nonetheless affected by global change drivers (Colom et al, 2019; Kuckerov et al, 2021). However, the annual 5.7% decline in abundance found doubles the maximum annual decline rates found in other studies, which range from −2.6% to −0.8% (see tab.…”
Section: Discussionsupporting
confidence: 87%
“…T A B L E 2 TAOc (community preference for open/closed habitats), STIc (community temperature index) and SPIc (community precipitation index) over time on each transect. nonetheless affected by global change drivers (Colom et al, 2019;Kuckerov et al, 2021). However, the annual 5.7% decline in abundance found doubles the maximum annual decline rates found in other studies, which range from À2.6% to À0.8% (see tab.…”
Section: Discussionmentioning
confidence: 55%
“…However, although declines in insect abundance and biomass have been shown in large-scale studies and syntheses 2 , 5 , 6 , trends in other biodiversity metrics have been less clear. Species richness, for example, has been found to decline along with abundance in some large studies 5 , 14 , whereas in other studies, insect richness was reported to be stable 6 , 7 .…”
Section: Mainmentioning
confidence: 89%
“…Here we examine the multidimensional nature of biodiversity trends in assemblages of terrestrial insects, arachnids (spiders and mites) and Entognatha (springtails and allies)—hereafter described collectively as ‘insects’, for brevity—during the past decades using a large compilation of insect surveys through time 18 . Although previous work has examined some of these multifaceted patterns for subsets of taxa (for example, butterflies 14 or hoverflies 16 ), locations 6 , 7 and/or habitat types 19 , our synthetic approach allows us to assess the prevailing trends in multiple biodiversity metrics from the openly available long-term insect assemblage data across locations, taxa and habitats. Our focus here is on terrestrial insects only, because two recent studies from Europe 20 and North America 21 have used extensive data compilations to assess changes to the diversity of freshwater invertebrates.…”
Section: Mainmentioning
confidence: 99%
“…For butterflies, declines have been widely reported, including in the UK, Netherlands, and grassland habitat across Europe [4]. In the United States, widespread declines have been reported, including the Midwest [5], with similar results using independent data in Ohio [6], and Illinois [7], but with the starkest declines in the Western US [8,9]. Exceptions to the general pattern of insect decline include no trends for aquatic insects globally, but this was controversial [10].…”
Section: Introductionmentioning
confidence: 99%